Improvement of water and nutrient efficiencies oil palm through bio-silicic acid application - Laksmita Prima SANTI; Adhy ARDIYANTO; Agung KURNIAWAN; Lilik A PRABOWO; Ian SEBASTIAN (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2021)
Crop water use efficiency is critical for high yields in conditions of limited water supplies. This study aims at determining the effect of application bio-silicic acid (BioSilAc) on water use efficiency and nutrient availability for immature (2 years after planting) and mature (5 years after planting) oil palms in sandy soil during a period of low rainfall. A field experiment was conducted on sandy soil at an oil palm plantation in Central Kalimantan. The experiment was arranged in a randomized block design with seven treatments and three replicates using a combination of composted empty fruit bunches of oil palm (CEFBOP) and BioSilAc applications. The treatments (tree-1 year-1) were as follows (tree-1 year-1): (T1) 100% NPK standard dosage; (T2) T1 + 1.5 kg quartz sand; (T3) 75% (T1) + 1.5 kg quartz sand; (T4) T1+ 4 tablets BioSilAc; (T5) 75% (T1) + 4 tablets BioSilAc; (T6) T1 + 50 kg CEFBOP + 2 tablets BioSilAc; and (T7) 75% (T1) + 50 kg CEFBOP + 2 tablets BioSilAc. The parameters observed were soil and leaf nutrient contents, average weight, and number of fresh fruit bunch (FFB), and daily water usage and water potential using a sap flow meter and stem psychrometer to calculate water use efficiency in T1 (control) and T5 which represents the application of BioSilAc. The results indicated that the application of 75-100% NPK + 4 tablets BioSilAc tree-1 year-1 in mature oil palm was capable of improving yield of11.9% (T5) and 12.1% (T4) and water use efficiency of 31.3% (mature) and 50.4% (immature) of the control treatment.